Liver Transplantation for Acute Liver Failure Attributed to Leptospirosis: A Report of Two Cases - Thibault Lebreton; Fréderic Aubrun; Jean-Yves Mabrut; Laurent Heyer; Camille Perrin (Case Reports in Critical Care)
Background. Leptospirosis is a zoonosis caused by pathogenic spirochetes of the genus Leptospira. Although it may be limited to nonspecific fever, leptospirosis may also be responsible for neurological symptoms or fulminant diseases such as Weil’s disease. Diagnosis is challenging due to the difficulty in isolating the organism and the delays required for performing the serological test. Case Presentation. Two cases of leptospirosis are presented here. The clinical picture differed from a real Weil’s disease in the first case and from a neuro-leptospirosis in the second. However, both patients underwent liver transplantation because of the severity of the associated acute liver failure. Unfortunately, one of the cases had a fatal outcome. Conclusion. Antibiotic treatment for leptospirosis should not be delayed by the lack of a positive serology test for this potentially lethal disease. In the context of a history of exposure to risk factors for leptospirosis, a negative serology must be repeated 7 days to 2 weeks following the first test. Although not always present, acute liver injury may, in rare cases, require liver transplantation.